Cover Picture: A Microstructured Graphene/Poly(N‐isopropylacrylamide) Membrane for Intelligent Solar Water Evaporation (Angew. Chem. Int. Ed. 50/2018). Issue 50 (14th November 2018) - Zhang, Panpan; Liu, Feng; Liao, Qihua; Yao, Houze; Geng, Hongya; Cheng, Huhu; Li, Chun; Qu, Liangti
Abstract : Solar water evaporation with a leaf‐like microstructured graphene/poly( N ‐isopropylacrylamide) (mG/PNIPAm) membrane is described by L. Qu and co‐workers in their Communication onpage 16343 ff. In response to varying sunlight intensities, the water evaporation rate of this leaf‐like mG/PNIPAm membrane is tuned through opening and closing of the water transport channels in a process reminiscent of the stomatal opening and closing of leaves. A double‐layer membrane variant can further tailor water loss through self‐curling.